Descriptive Memoir of the Ministry of Railways, April 1956 - Planning Commission (Planning Commission, 1956)
The Railway Board functions as Ministry of the Government of India and exercises all the powers of the Central Government in respect of regulation, construction, maintenance and operation of railways. By virtue of inclusion of the Financial Commissioner for Railways in its constitution, the Railway Board also exercises the full powers of the Government of India in regard to railway expenditure. These powers are derived from the provisions of the Indian Railway Board Act of 1905, the Indian Railway Act, 1890, and the Constitution. the existing constitution of the Railway Board also gives the Board such freedom in shaping and carrying out railway policy as will enable it to treat railways as a national undertaking to be developed on commercial lines.
Organisation and Methods Division Cabinet Secretariat